The yield curve as a predictor of recessions in the Euro Area: A multicountry analysis - Cruz, João Pedro de Brito (2016)
This paper revisits the role of the yield spread to forecast recessions in the Euro Area. We show that the contribution of the spread can be decomposed into the effect of future expected changes in short term rates and the effect of the term premium. This decomposition is achieved with the use of a no arbitrage affine term structure model incorporating two latent factors that explain level and slope movements in the yield curve. We find that the expectations hypothesis component accounts for most of the predictability of the spread with part of this predictability reflecting the effects of the monetary policy stance. The results suggest, however, that the yield spread predictive content is driven by other factors independent of monetary policy.